2013
DOI: 10.1073/pnas.1300805110
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dll4 regulation reveals a combinatorial role for Sox and Notch in arterial development

Abstract: The mechanisms by which arterial fate is established and maintained are not clearly understood. Although a number of signaling pathways and transcriptional regulators have been implicated in arterio-venous differentiation, none are essential for arterial formation, and the manner in which widely expressed factors may achieve arterial-specific gene regulation is unclear. Using both mouse and zebrafish models, we demonstrate here that arterial specification is regulated combinatorially by Notch signaling and Sox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(190 citation statements)
references
References 36 publications
6
180
2
Order By: Relevance
“…We found that the DLL4 locus contains multiple conserved ERG-bound enhancers, including regions ∼12 kb upstream of the transcriptional start site (TSS) and within intron 3 (Fig. 8A), both of which were previously shown to have arterialspecific activity in vivo (Sacilotto et al, 2013;Wythe et al, 2013). We also identified an ERG-bound enhancer, conserved in cows and humans, ∼3.0 kb upstream of the gene H2.0-like homeobox (HLX) ( Fig.…”
Section: Erg Regulates a Network Of Constitutive And Vegf-inducible Gmentioning
confidence: 74%
“…We found that the DLL4 locus contains multiple conserved ERG-bound enhancers, including regions ∼12 kb upstream of the transcriptional start site (TSS) and within intron 3 (Fig. 8A), both of which were previously shown to have arterialspecific activity in vivo (Sacilotto et al, 2013;Wythe et al, 2013). We also identified an ERG-bound enhancer, conserved in cows and humans, ∼3.0 kb upstream of the gene H2.0-like homeobox (HLX) ( Fig.…”
Section: Erg Regulates a Network Of Constitutive And Vegf-inducible Gmentioning
confidence: 74%
“…These observations support the notion that, as shown in the caudal fin regeneration model (24), once the vascular plexus is formed, some vessels gain arterial identity. To further test whether arterial specification is a late event during revascularization, we developed an arterial-specific reporter line by using a previously described enhancer of the mouse Dll4 gene (26), Tg(Dll4in3:TagRFP). This line expresses TagRFP specifically in arterial endothelium in both embryos ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in vitro studies reported that SoxF transcription factors can bind the arterial-specific enhancer of the notch ligand dll4 (Sacilotto et al, 2013). As Hey2 and Efnb2a/b have been suggested to act downstream of Notch signaling (Lawson et al, 2001) and as we show here that sox7 genetically interacts with both factors, we wondered whether the arterial defects in sox7 mutants are a consequence of altered Notch signaling levels.…”
Section: Increased Arterial Notch Signaling Suppresses the Vascular Dmentioning
confidence: 80%
“…One subgroup of the Sox family that is of particular interest for vascular development is the SoxF group, consisting of SOX7, SOX17 and SOX18. In vitro studies revealed that SoxF transcription factors can bind the arterial-specific enhancer of the Notch ligand dll4 (Sacilotto et al, 2013). Furthermore, Sox17 has recently been shown to play a key role in endoderm formation, hematopoietic stem cell regulation and the acquisition of arterial identity by functioning upstream of Notch signaling (Hudson et al, 1997;Kanai-Azuma et al, 2002;He et al, 2011;Corada et al, 2013).…”
Section: Introductionmentioning
confidence: 99%